Sequential bilateral retinal artery occlusion - Padrón-Pérez N (Dove Medical Press, 2014)
Noel Padrón-Pérez,1 Janny Rosario Aronés,2 Silvia Muñoz,1 Luis Arias-Barquet,1 Jorge Arruga1,31Department of Ophthalmology, Hospital Universitari de Bellvitge, 2Hospital de l'Esperança – Parc de Salut Mar, 3Institut Català de Retina, Barcelona, SpainAbstract: An 86 year old woman experienced a sequential bilateral loss of vision over a period of less than 24 hours. Clinical findings and complementary studies suggested a bilateral atherogenic embolic event. Initially, she presented a superior branch retinal artery occlusion in her right eye followed by a central retinal artery occlusion with cilioretinal artery sparing in her left eye. Some conservative maneuvers performed did not improve visual acuity in the left eye. Supra-aortic Doppler ultrasonography revealed mild right internal carotid artery stenosis and moderate left internal carotid artery stenosis with a small, smooth, and homogeneous plaque. The transthoracic echocardiography showed a severe calcification of the mitral valve with a mild-moderate rim of stenosis. Central retinal artery occlusion and branch retinal artery occlusion are characterized by painless monocular loss of vision. Clinical approach and management attempt to treat the acute event, find the source of the vascular occlusion, and prevent further vascular events from occurring. Giant cell arteritis is a potentially treatable cause of central retinal artery occlusion and should be excluded in every single patient over 50 years old.Keywords: loss of vision, branch retinal artery occlusion, central retinal artery occlusion, Hollenhorst plaque